Higher frequency of peripheral blood CD103+CD8+ T cells with lower levels of PD-1 and TIGIT expression related to favorable outcomes in leukemia patients - Liu, Lian; Lai, Wenpu; Zhuo, Xiaoling; Chen, Sihui; Luo, Xiaodan; Tan, Huo (Frontiers in Immunology, 2024)
Background: Leukemia is a prevalent pediatric life-threatening hematologic malignancy with a poor prognosis. Targeting immune checkpoints (ICs) to reverse T cell exhaustion is a potentially effective treatment for leukemia. Tissue resident memory T (TRM) cells have been found to predict the efficacy of programmed death receptor-1 inhibitor (anti-PD-1) therapy in solid tumors. However, the IC characteristics of TRM cells in leukemia and their relationship with prognosis remain unclear.We employed multi-color flow cytometry to evaluate the frequencies of CD103 + CD4 + and CD103 + CD8 + T cells in the peripheral blood (PB) of patients with acute myeloid leukemia and B-cell acute lymphoblastic leukemia compared to healthy individuals. We examined the expression patterns of PD-1 and T cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT) within the circulating CD103 + T cell subsets affected by leukemia. To further elucidate the immunological landscape, we assessed the differentiation status of CD103 + T cells across various disease states in patients with leukemia. Results: Our findings showed a significant increase in the frequency of CD103 + CD8 + T cells in the PB of patients with leukemia who had achieved complete remission (CR) compared to those in the de novo (DN) and relapsed/refractory (RR) stages. This increase was accompanied by a notable decrease in the expression levels of PD-1 and TIGIT in CD103 + CD8 + T cells in the CR stage. Additionally, our analysis revealed a higher proportion of CD103 + CD8 + T cells in the central memory (TCM) and effector memory (TEM) subsets of the immune profile. Notably, the proportions of CD103 + naï ve T cells, CD103 + TEM, and CD103 + terminally differentiated T cells within the CD8 + T cell population were significantly elevated in patients with CR compared to those in the DN/RR stages. Conclusion: The data indicate that circulating higher frequency of CD103 + CD8 + T cells with lower expression of PD-1 and TIGIT are associated with favorable outcomes in patients with leukemia. This suggests a potential role of TRM cells in leukemia prognosis and provides a foundation for developing targeted immunotherapies.